1993
DOI: 10.1152/jappl.1993.74.1.186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced O2 delivery with anemia, hypoxia, or ischemia on peak VO2 and force in skeletal muscle

Abstract: This investigation was designed to describe alterations in O2 uptake (VO2) and tension development in a contracting in situ gastrocnemious-plantaris muscle preparation during three conditions of reduced O2 delivery [arterial O2 concentration X blood flow (Q)]. The three conditions, hypoxemia (H), ischemia (I), and anemia (A), were matched for O2 delivery. A normoxic normal flow condition was also utilized for comparison. H was produced by respiring the animals with 9% O2 in N2; I was produced by lowering Q, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 0 publications
5
29
0
Order By: Relevance
“…As has been demonstrated previously (2,6,9,13,26), as blood flow was reduced in the present study the muscle was able to extract a higher percentage of the O 2 delivered by convective blood flow. A greater diffusion of O 2 to the mitochondria (for a higher extraction) was likely accomplished by reductions in intracellular PO 2 .…”
Section: Skeletal Muscle Bioenergetics After Blood Flow Reductionsupporting
confidence: 87%
See 1 more Smart Citation
“…As has been demonstrated previously (2,6,9,13,26), as blood flow was reduced in the present study the muscle was able to extract a higher percentage of the O 2 delivered by convective blood flow. A greater diffusion of O 2 to the mitochondria (for a higher extraction) was likely accomplished by reductions in intracellular PO 2 .…”
Section: Skeletal Muscle Bioenergetics After Blood Flow Reductionsupporting
confidence: 87%
“…The present study demonstrated that when O 2 availability was reduced after normal steadystate conditions had been reached (fully aerobic contractions), the tight coupling of force production to respiration was maintained (see Fig. 3), as has been shown before in this highly oxidative muscle for moderate ischemia conditions (2,6,8,9,26). Muscle [ATP], [PCr], and lactate efflux during the I condition were not significantly different from the values seen at the same stimulation intensity with normal blood flow.…”
Section: Skeletal Muscle Bioenergetics After Blood Flow Reductionsupporting
confidence: 83%
“…PvO2 was less in H than I hearts, even at the same QO2, according to observations obtained by others in skeletal muscle (Hogan et al, 1992;Dodd et aL, 1993). It is difficult to assess whether this phenomenon is due to non-uniform perfusion secondary to low CPP in I hearts or to lactate-driven downregulation.…”
Section: Performance During 02 Shortagementioning
confidence: 68%
“…Low hemoglobin levels may influence oxygen delivery to skeletal muscle, and Figure 1. Adjusted* AMT mean scores (and 95% confidence intervals) for different hemoglobin levels, above and below the WHO anemia cut-points n ¼ Number of participants *Adjusted for age, gender, smoking, education, BMI, COPD, cerebrovascular disease, congestive heart failure, peptic ulcer, dementia, depression, hypertension, Charlson's Index, creatinine, ACE-inhibitors, antibiotics, corticosteroids, NSAIDs consequently negatively impact on muscular strength (Dodd et al, 1993) possibly as reported in respiratory disorders patients (Mador and Bozkanat, 2001;Sauleda et al, 2003). Chronic hypoxia is also responsible for pathophysiological changes leading to the onset or worsening of disabling processes (Silverberg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%